The United States Supreme Court and the death penalty since Furman: The settlement of basic issues - Moore, Richter H. (American journal of criminal justice, 1984)
In 1972 the United States Supreme Court in Furman V. Georgia found that the death penalty as it was then being applied was cruel and unusual punishment in violation of the Eighth and Fourteenth Amendments of the United States Constitution. Furman provided few constitutional guidelines, but states reinacted their death penalty statutes. In 1976 the Court began to receive appeals from death sentences imposed under the reinacted statutes. In its decisions the Court began to establish guidelines. It found the death penalty was not per se cruel and unusual punishment. Before the death penalty can be imposed the court must take into consideration any mitigating circumstances and the case must be reviewed by the state supreme court. A mandatory death sentence is unconstitutional. Other issues including proportionality, due process and finality of judgment will be examined in the next segment of this study.